Navigating Institutional Pressures and Cognitive Aspects: Strategies for Sustainable Corporate Performance in Creative Industries - Ishkak, Iskhak; Wibowo, Setyo Ferry; Suparno, Suparno (Bright Publisher, 2026)
This study examines the relationship between institutional pressures and corporate performance through the lens of corporate cognitive aspects in the Indonesian creative industry sector. Data were collected from 531 business owners across fashion, food, and crafts sectors and analyzed using Structural Equation Modeling Partial Least Squares (SEM–PLS). The results show that institutional pressures significantly affect digital transformation (β = 0.656, p 0.001), entrepreneurial orientation (β = 0.748, p 0.001), dynamic capability (β = 0.660, p 0.001), and competitive advantage (β = 0.759, p 0.001). However, the direct effect of institutional pressures on corporate performance is not significant (β = 0.039, p = 0.231). Instead, digital transformation (β = 0.347, p 0.001), entrepreneurial orientation (β = 0.146, p = 0.007), and dynamic capability (β = 0.446, p 0.001) mediate the relationship, explaining 65% of the variance in corporate performance (R² = 0.65). This study contributes to the literature by highlighting the role of corporate cognitive aspects and emphasizing the integration of institutional theory into entrepreneurial practice. Moreover, it aligns with Sustainable Development Goals (SDGs) 9 and 12 by promoting responsible consumption and innovation in industry. One limitation of this study lies in its focus on Indonesia’s creative sector, suggesting that future research should explore broader contexts. The findings encourage businesses to adopt corporate cognitive aspects to achieve sustainable growth. Future studies could also investigate additional antecedents of corporate cognitive aspects and their influence on environmental performance.